QoS aware task consolidation approach for maintaining SLA violations in cloud computing. (April 2022) - Singh, Pardeep; Prakash, Vijay; Bathla, Gourav; Singh, Rahul Kumar
Highlights: The proposed approach defines virtual machines (VMs) clusters. Cluster formation is done based on the mean value of available resources. Formation of different clusters of tasks based on average resource requirements. Proposed approach can reduce the number of migrations by up to 67.9%. MTC approach can achieve up to 61.4% less SLA violation time per active host and 35.3% reduction over SLA violations. Abstract: This paper aims to achieve a better Quality of Service (QoS) through Modified Task Consolidation (MTC) approach. The proposed MTC approach defines virtual machines (VMs) clusters based on the mean value of available resources and forms different clusters of tasks based on average resource requirement. These clusters of tasks and VMs help to make an appropriate mapping among tasks and VMs as per the suitability of CPU and memory resources. The approach has also considered tasks' bandwidth requirements and prioritizes them over the VMs with high bandwidth availability during cluster-wise mapping. Comprehensive simulations have been performed to analyze the performance of the proposed scheme, and results have been examined for different configurations over two real-time workloads. The result analysis has revealed that the proposed approach can reduce the number of migrations by up to 67.9%. Furthermore, it can reduce performance degradation due to migration up to 60%. Also, compared to the state-of-the-art approaches, the MTC approach can achieve up to 61.4% less SLA violation time per active host (SLATHAH) and up to 35.3% reduction Over SLA violations (OSLAV). Graphical abstract: Image, graphical abstract